Multi-Locus Phylogeny and Taxonomy of the Fungal Complex Associated With Rusty Root Rot of Panax ginseng in China - Guan, Yi Ming; Ma, Ying Ying; Jin, Qiao; Wang, Qiu Xia; Liu, Ning; Fu, Yong Ping; Zhang, Ya Yu; Li, Yu (Frontiers in Microbiology, 2020)
Panax ginseng rusty root rot caused by the Ilyonectria species complex is a devasting disease, and it is one of the main factors contributing to the difficulty in continual cropping. Rusty root rot occurs in all ginseng fields, but little is known about the taxonomy of the fungal pathogen complex, especially Ilyonectria and Ilyonectria-like species. Rusty root rot samples from commercial ginseng cultivation areas of China were collected, and the pathogens were isolated and purified as single spores. Based on the combination analysis of multiple loci (rDNA-ITS, TUB, HIS3, TEF, ACT, LSU, RPB1, RPB2 and SSU) and morphological characteristics, the pathogens causing ginseng rusty root rot was determined. Fungal isolates were obtained from infected roots in 56 locations of main cultivation areas in China. A total of 766 strains were identified as Ilyonectria, Ilyonectria-like and Rhexocercosporidium species, including I. robusta (55.0%), I. communis (21.7%), I. mors-panacis (10.9%), I. pseudodestructans (2.0%), I. changbaiensis (1.3%), I. qitaiheensis (1.3%), Neonectria obtusispora (2.0%), Dactylonectria torresensis (0.5%), D. sp. (0.5%) and R. panacis (1.5%), and four novel species, Thelonectria. ginsengicola (1.0%), T. jixiensis (1.0%), T. mulanensis (0.8%) and T. fusongensis (0.5%), a total of 14 species. I. robusta was the most prevalent and damaging species as the highest proportioned pathogen, which is different from the pathogens reported previously. All strains were proven to cause ginseng rusty root rot. Our results indicated that the taxonomy of the fungal complex associated with ginseng rusty root rot, including Ilyonectria, Ilyonectria-like (Dactylonectria, Neonectria, Thelonectria) and Rhexocercosporidium.